ANALISIS PEMBELAJARAN BERBASIS HOTS PADA PESERTA DIDIK KELAS XI TKR DI SMK NEGERI 2 SUKOHARJO - Erva Nhor Juliana; Suharno Suharno; Nyenyep Sriwardani (Nozel : Jurnal Pendididikan Teknik Mesin, 2019)
The objective from this research is to find Penelitian ini bertujuan untuk: (1) how the learning implementation design (RPP) made by TKR teachers at SMK Negeri 2 Sukoharjo that meets Higher Order Thinking Skills elements; (2) implementation of learning activities carried out by TKR teachers at SMK Negeri 2 Sukoharjo; (3) implementation of learning assessments made by TKR teachers at SMK Negeri 2 Sukoharjo which leads to elements of higher order thinking skills. This research is a mixed methods research. Data sources came from 98 students from TKR XI, Teachers of Smk Negeri 2 Sukoharjo. Data techniques include questionnaires, documentation and observation. This study uses data validity using sampling techniques and the Slovin formula. The research procedure consists of research methods, preparation of research instruments, data collection, data analysis, drawing conclusions. The conclusion is (1) The Learning Implementation design (RPP) made by TKR class XI teachers at SMK Negeri 2 Sukoharjo has damaged it to fulfill the elements of higher-order thinking skills; (2) The implementation of learning activities by TKR teachers at SMK Negeri 2 Sukoharjo has attempted to implement learning activities that lead to higher-order thinking skills; (3) The assessment or evaluation of learning made by TKR teachers at SMK Negeri 2 Sukoharjo has led to elements of measuring higher-order thinking skills.